2017
DOI: 10.1371/journal.pone.0174118
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features, outcomes and genetic characteristics of hypertrophic cardiomyopathy patients with severe right ventricular hypertrophy

Abstract: IntroductionSevere right ventricular hypertrophy (SRVH) is a rare phenotype in hypertrophic cardiomyopathy (HCM) for which limited information is available. This study was undertaken to investigate the clinical, prognostic and genetic characteristics of HCM patients with SRVH.MethodsHCM with SRVH was defined as HCM with a maximum right ventricular wall thickness ≥10 mm. Whole-genome sequencing (WGS) was performed in HCM patients with SRVH. Multivariate Cox proportional hazards regression models were used to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…III4 experienced sudden death18 months after surgical septal myectomy and II5 was recommended to have an ICD implantation. Third, previous works showed that areas of focal fibrosis identified by LGE was associated with prognosis in HCM 22 , diffuse fibrosis detected by ECV had significant association to fibrosis measured histologically 2325 , and different morphological subtype of hypertrophic cardiomyopathy could have diverse prognosis 2628 . In the present study, the 8 HCM phenotypically positive and 1 borderline affected individuals had variable morphological subtypes, focal fibrosis by LGE, and diffuse fibrosis by ECV, which provided strong evidence for variable phenotypes associated with the same genotype.…”
Section: Discussionmentioning
confidence: 89%
“…III4 experienced sudden death18 months after surgical septal myectomy and II5 was recommended to have an ICD implantation. Third, previous works showed that areas of focal fibrosis identified by LGE was associated with prognosis in HCM 22 , diffuse fibrosis detected by ECV had significant association to fibrosis measured histologically 2325 , and different morphological subtype of hypertrophic cardiomyopathy could have diverse prognosis 2628 . In the present study, the 8 HCM phenotypically positive and 1 borderline affected individuals had variable morphological subtypes, focal fibrosis by LGE, and diffuse fibrosis by ECV, which provided strong evidence for variable phenotypes associated with the same genotype.…”
Section: Discussionmentioning
confidence: 89%
“…In an early study, using transthoracic echocardiography, RV hypertrophy was reported in 44% of patients with HCM 10 . Studies using CMR demonstrated a prevalence ranging from 1.3 to 30%, depending on the criteria of RV involvement 4 , 5 , 11 . Our study showed a prevalence of 14.4%, with the RVMWT ≥ 7 mm on CMR.…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely accepted that HCM is a disease involving both cardiac ventricles rather than being morphologically limited to the left ventricle. The incidence of RV hypertrophy in patients with HCM is 30%-53% as shown by CMR imaging and echocardiography studies (6,7,9,11), whereas SRVH is relatively uncommon (prevalence of 1.3%) (12). In our study, among the 1,316 patients with HCM who underwent LGE CMR imaging Previous studies have identified a significant correlation between the maximum RV and LV wall thickness (7).…”
Section: Discussionmentioning
confidence: 49%